Partial Atomic Tin Nanocomplex Pillared Few-Layered Ti3C2Tx MXenes for Superior Lithium-Ion Storage - Zhang, Shunlong; Ying, Hangjun; Yuan, Bin; Hu, Renzong; Han, Wei‑Qiang (Nano-Micro Letters, 2020)
MXenes have attracted great interest in various fields, and pillared MXenes open a new path with larger interlayer spacing. However, the further study of pillared MXenes is blocked at multilayered state due to serious restacking phenomenon of few-layered MXene nanosheets. In this work, for the first time, we designed a facile NH4+ method to fundamentally solve the restacking issues of MXene nanosheets and succeeded in achieving pillared few-layered MXene. Sn nanocomplex pillared few-layered Ti3C2Tx (STCT) composites were synthesized by introducing atomic Sn nanocomplex into interlayer of pillared few-layered Ti3C2Tx MXenes via pillaring technique. The MXene matrix can inhibit Sn nanocomplex particles agglomeration and serve as conductive network. Meanwhile, the Sn nanocomplex particles can further open the interlayer spacing of Ti3C2Tx during lithiation/delithiation processes and therefore generate extra capacity. Benefiting from the “pillar effect,” the STCT composites can maintain 1016 mAh g−1 after 1200 cycles at 2000 mA g−1 and deliver a stable capacity of 680 mAh g−1 at 5 A g−1, showing one of the best performances among MXene-based composites. This work will provide a new way for the development of pillared MXenes and their energy storage due to significant breakthrough from multilayered state to few-layered one. Highlights: 1 A facile NH4+ method was proposed to prepare Sn nanocomplex pillared few-layered Ti3C2Tx MXene nanosheets. 2 The MXene nanosheets showed excellent lithium-ion storage performances among MXene-based materials, which can maintain 1016 mAh g−1 after 1200 cycles at 2000 mA g−1 and deliver a stable capacity of 680 mAh g−1 at 5 A g−1.